Autorzy:Aleksandra Ciszkowska, Alina Przychoda, Zygmunt Łaszczyk
Wydawnictwo:WSiP
Rok wydania:2012
Oblicz: a) -³√-8* ⁵√-32 +√2*√24.5 gwiazdek na podstawie 6 opinii

`a) \ \ \ (-root(3)(-8)*root(5)(-32)+sqrt2*sqrt2)/(sqrt(16/3)*root(3)(-27) *sqrt3)= `   `(-(-2)*(-2)+sqrt4)/(sqrt16/sqrt3*(-3)*sqrt3)=`  `(-4+2)/(4/strikesqrt3*(-3)*strikesqrt3)=(-2)/(-12)=1/6`  

`b) \ \ \ (root(3)(-27)*sqrt(16/9) +root(7)(-1) *sqrt25: root(3)(-125/64))/(root(3)(343)=`  `=(-strike3*4/strike3+(-1)*5:(-5/4))/7=`   

`=(-4+(-5)*(-4/5))/7=`   `(-4+4)/7=0/7=0`